2011
DOI: 10.1097/hjh.0b013e32834d2532
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac benefits of exercise training in aging spontaneously hypertensive rats

Abstract: Low to moderate-intensity chronic ExT reverses the cardiac alterations associated with hypertension: myocardial arteriole, left ventricle hypertrophy, collagen content and tachycardia. These changes could be consequence or cause of the reduction in BP observed in trained SHR. In addition, ExT does not worsen the underlying inflammatory burden associated with hypertension. Therefore, the data support a beneficial effect of ExT in aging SHR similar to that reported in young or middle-aged individuals, confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 49 publications
5
34
0
10
Order By: Relevance
“…Improved functional capacity in SHR occurred despite a slight increase in arterial blood pressure compared to SHR-SED. The effects of exercise on SHR blood pressure are variable; some authors have shown an anti-hypertensive effect of exercise [19], others found hypertension unchanged [52,53] or even exacerbated [54]. The low intensity exercise protocol did not change body weight.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Improved functional capacity in SHR occurred despite a slight increase in arterial blood pressure compared to SHR-SED. The effects of exercise on SHR blood pressure are variable; some authors have shown an anti-hypertensive effect of exercise [19], others found hypertension unchanged [52,53] or even exacerbated [54]. The low intensity exercise protocol did not change body weight.…”
Section: Discussionmentioning
confidence: 98%
“…We therefore conclude that long-term physical exercise attenuated increase in myocardial collagen content and lysyl oxidase gene expression. It has previously been shown that exercise training in both normotensive and hypertensive aging rats attenuates myocardial fibrosis and modulates myocardial collagen gene expression [19,59]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…us one of the major bene�ts of exercise training in hypertension is the preservation of cardiomyocyte cell number. Despite the potential for exercise training to increase myocardial mass in pressure overload, most studies have reported an improved phenotype aer training [25,30,46,61,[80][81][82][83][84][85][86][87]. One of the most proli�c bene�ts of exercise training is its improvement on adrenergic signaling.…”
Section: Cardiac Remodelingmentioning
confidence: 99%